Promoting Executive Function Skills in Preschoolers Using a Play-Based Program - Gibb, Robbin; Coelho, Lara; Van Rootselaar, Nicole Anna; Halliwell, Celeste; MacKinnon, Michelle; Plomp, Isabelle; Gonzalez, Claudia L. R. (Frontiers in Psychology, 2021)
In recent years, play has been shown to be a powerful means to enhance learning and brain development. It is also known that through play children enhance their executive function (EF) skills. Furthermore, well-developed EF in preschoolers has been shown to be an important predictor for later academic and life success. Armed with this information a program, Building Brains and Futures, for developing EF through play was designed for 3-5-year-olds. The program consisted of ten simple, fun, and interactive games selected to enhance various facets of EF. The ten games included were: dimensional change card sort, lips and ears, block building, musical freeze, opposites, pretend play, red light/green light, shared project, Simon says, and wait for it. The program was implemented with a group of children shown to have challenges with respect to kindergarten readiness. The approach was first, to build adult capability by sharing knowledge of brain development, EF, and the importance of play with educators, caregivers, and parents. Second, to build skills in delivering the program in the school setting. Children engaged with the program of games for a minimum of six weeks. Their performance on a battery of direct measures (rather than parent/caregiver report) of EF, language, and motor skills, were recorded before and after the program. The results showed improvement in all three domains. In addition, adopters of the BBF program reported it was easily and successfully integrated into their existing preschool curricula. The importance of intentional adult directed play in building developmental learning, including EF, is discussed.